Service Quality, Company Image And Location Affect To Customer Loyalty Case Of : Bank Jatim Main Branch Surabaya - Amin Mahmudi; Ani Wulandari; Arasy Alimudin (Jurnal Ekonomi, 2021)
This study aims to determine the effect of the variables of Service Quality, Company Image and Location on Customer Loyalty at Bank Jatim Main Branch Surabaya. This research was conducted with quantitative methods. The data studied are primary data obtained directly from the company in the form of questionnaire results with a sample of 100 respondents from bank Jatim customers, the main branch of Surabaya and analyzed using SPSS version 25 for windows. The data were tested using the classical assumption test, namely: normality, multicollinearity, and heteroscedasticity. Then tested using t test, f test and determination test R2. The results showed that the variables of Service Quality, Company Image, and Location partially had a significant positive effect. Simultaneously seen from the test results, the F value of 15,889 with a value of sig = 0.000 shows that it is smaller than the value of = 0.050 (0.000 < 0.050) which means that the service quality variable (X1), company image (X2), location (X3) simultaneously significant effect on Service Quality.